Big Data, Data Mining and Machine Learning - Jared Dean (Wiley, 2014)
This book provides a comprehensive view on the recent trend toward high performance computing architectures especially as it relates to analytics and data mining. Topics that are covered include: big data (and its characteristics), high performance computing for analytics, massively parallel processing (MPP) databases, algorithms for big data, in-memory databases, implementation of machine learning algorithms for big data platforms and analytics environments. However none gives a historical and comprehensive view of all these separate topics in a single document.